The Relationship among GDP, Carbon Dioxide Emissions, Energy Consumption, and Energy Production from Oil and Gas in Saudi Arabia - Algarini, Abdullah (International Journal of Energy Economics and Policy, 2019)
The purpose of this paper is to investigate the causal relationship among economic growth, CO2 emissions, energy consumption, and energy production from oil and gas during 1990 to 2017. By Vector autoregressive models and Granger causality Wald tests, this study suggests that there is bidirectional relationship between: economic growth and energy consumption, economic growth and CO2 emissions, and electricity production from gas and CO2 emissions. Moreover, there is a unidirectional causality runs from energy consumption and CO2 emission to growth of electricity production from gas, and from energy production from oil to growth of CO2 emissions. This result confirms that energy consumption is a critical input of production and plays as a complement to the important factors of labor, capital, and land in Saudi Arabia. Keywords: Energy consumption, Energy production, Economic growth, Saudi Arabia. JEL Classifications: C32, O13, Q43 DOI: https://doi.org/10.32479/ijeep.8345